Budidaya Cacing Sutra (Tubifex sp.) dan Budidaya Ikan Lele Menggunakan Sistem Bioflok di Kecamatan Simpenan, Sukabumi - Santi Febrianti; Dadang Shafruddin; Eddy Supriyono (Jurnal Pusat Inovasi Masyarakat (PIM), 2020)
Silk worms (Tubifex sp.) Is a natural food that is widely used as fish food. The nutritional content of silk worms consisting of protein reaches 57%, fat 13.3%, crude fiber 2.04%, ash content 3.6% and water 87.7%. Silk worms contain 13 kinds of amino acids, namely 7 essential amino acids and 6 non-essential amino acids. The study was conducted in Cidadap Village, Pelabuhan Ratu, Sukabumi in August 2019. This research was conducted to find out and obtain the best composition of maintenance media to increase the growth of Silkworm (Tubifex sp) population through efforts to utilize organic wastes of catfish farming so that their utilization more optimal. The method used in this activity is cultivation using fiber pool. Cidadap and Loji villages have enormous potential to cultivate silk worms (Tubifex sp.). Cidadap Village is one area that needs Silk Worms (Tubifex sp) to support glass eel cultivation activities, so that the results of this cultivation are very utilized. Silkworm cultivation carried out together with the cultivation of catfish with a biofloc system gives good results for the growth of silkworm biomass (Tubifex sp.). Keywords: Silk worms (Tubifex sp), biofloc, fish feed